STRATEGI PEMERINTAH DALAM MENGURANGI PENGGANGGURAN DI KABUPATEN SIAK TAHUN 2011-2013 - Febrianda, Rudi; Ridwan, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Unemployment could only be solved by national development which is intended to achieve economic growth and social through creating employment opportunities and use their labor in the right place and adequate. Continuing high figure of unemployment in Siak Regency due to some of the one of them is that there is an indication information system that is not transparent information delivery job opportunities available to job seekers. Not enforced transparency and lack of communication between provider safety with job seekers has led to job seekers difficulties to get information on job opportunities offered by provider safety problems or are. How this strategy The Government to reduce unemployment in Siak Regency in 2011-2013 and what obstacles in carrying out its strategies the government to reduce unemployment in Siak Regency in 2011-2013?Types of research that used in this research is qualitative research . Location in this research is in the location or was to take in the region Siak Regency with 12 people as informers in this research. Technical data collection that is used; an interview, observation and documentation. After the data obtained together, and ordered and classified the focus of his research and theme. Penganalisaan data in this research by the descriptive qualitative research, namely by means of giving the impression in general from the research that produce data about the words orally and in writing and behaviors that can be observed the variables are examined and served with an explanation and the explanation based on data research results.Based on the results of research it can be concluded that the Government's trategi in reducing unemployment in Siak Regency in 2011-2013, is job canvassing, job expo, dissemination information of job market, is not going to the fullest because the Government is Social Service Manpower and Transmigration Siak Regency too focused on the number of workers who are registered in yellow cards, whereas the number of which was not been counted more than the been counted. The question and in this research to be able to run a strategy that will be done with maximum need to carry out the socialization to the public to be diligent search for information and want to come to job market and guidelines on conditions of safety.Key words : Strategy, The Government, Siak Regency, Unemployment